"Not a Big Climate Change Guy" Semiotic Gradients and Climate Discourse. Issue 1 (2nd January 2022) - Adams, Paul C.
ABSTRACT: This study explores the comparative grounds people employ to understand weather and climate, recognizing weather change while distancing themselves from climate change. It draws on interviews with farmers and ranchers in the Texas panhandle and West Texas, confirming previous research that rejects the idea of a knowledge gap or information deficit leading to misunderstanding of climate change. The semiotic method extends findings of media frame analysis and critical discourse analysis, showing how climate contrarianism employs semiotic gradients as people attach scales to sense of place, environmental process and personal identity. This scaling process clarifies why rural communication avoids the term "climate" while accentuating local, practical and weather-based responses.